Yield Line Analysis of Column Webs with Welded Beam Connections - Stockwell Jr., Frank W. (Engineering Journal, 1974)
In welded construction the connections, for the most part, are easily designed and fabricated. However, one of the more difficult connections occurs when a beam must be welded to a column web. This is so for two reasons: (1) analyzing the column webs capacity is arduous and (2) making the actual connection in accordance with the design is no simple task because of the space restrictions imposed on the welder by the column flanges. This paper will deal only with the first consideration—analyzing the column web strength—using Yield Line Analysis. The Yield Line approach has been utilized previously by Abolitz and Warner1 for brackets welded to column webs, and by Blodgett for welding rolled sections to box columns. The assumptions used here differ somewhat from those of the above authors. The final result is a series of curves covering a very high percentage of restrained beam to column web connections involving hot rolled shapes. The curves relate beam moments to column web thickness for a series of beam sizes and for W14 columns with yield strengths of 36 and 50 ksi. For special cases not covered by these curves, but for which the yield line pattern assumed is valid, direct solutions may be developed by use of the formulas used to construct these curves.